Formation of physical qualities in young basketball players - Sablin, A. B.; Kornishin, I. I.; Ulyanova, E. A.; Khvostenko, S. Yu. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to increase the physical fitness of basketball players aged 13-14 years at the initial stage of the general education training cycle.